2021
DOI: 10.1029/2020gl092084
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots of Glacier Mass Balance Variability in Central Asia

Abstract: The Tien Shan and Pamir mountains host over 28,000 glaciers providing essential water resources for increasing water demand in Central Asia. A disequilibrium between glaciers and climate affects meltwater release to Central Asian rivers, challenging the region's water availability. Previous research has neglected temporal variability. We present glacier mass balance estimates based on transient snowline and geodetic surveys with unprecedented spatiotemporal resolution from 1999/00 to 2017/18. Our results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 74 publications
6
42
0
Order By: Relevance
“…However, over the 18 years, the cumulative difference is only 0.69 m w.e. A comparison with the mass balance observations for the overlapping period shows that the reconstructed mass balance from Barandun et al (2021) deviates strongly in some years, while our model results are more in line with the observations. For example, for the 2015-2016 balance year, MB measurements revealed a mean specific mass balance of −0.39 m w.e.…”
Section: Comparison With Other Mass Balance Studiessupporting
confidence: 83%
See 4 more Smart Citations
“…However, over the 18 years, the cumulative difference is only 0.69 m w.e. A comparison with the mass balance observations for the overlapping period shows that the reconstructed mass balance from Barandun et al (2021) deviates strongly in some years, while our model results are more in line with the observations. For example, for the 2015-2016 balance year, MB measurements revealed a mean specific mass balance of −0.39 m w.e.…”
Section: Comparison With Other Mass Balance Studiessupporting
confidence: 83%
“…In contrast, the meteorological gradients (especially the precipitation gradient) are more variable and constraining these is more complex. Such climatological variability was also observed in a recent study of Barandun et al (2021) which revealed a complex climate-glacier interplay in the study area. This likely hampers the model to be applied for glaciers for which there are no or insufficient quality observations to tune the gradients.…”
Section: Calibrated Values For C 0 C 1 and Meteorological Gradientssupporting
confidence: 80%
See 3 more Smart Citations